RELEVANSI MATIRAGA SANTO VINSENSIUS DALAM PEMBENTUKAN KARAKTER MAHASISWA DI RUMAH BINA KARYA ILAHI - Sinong, Melania; Dewantara, Agustinus Wisnu (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2025)
The purpose of this study is to determine how the concept of Saint Vincent's mortification can contribute to the education and character development of prospective catechists and prospective religious teachers. This study is expected to provide in-depth insight into how values ​​such as self-denial, love for God and others, and the spirit of uniting oneself with Jesus Christ can be applied in everyday life by prospective catechists and religious teachers. This study uses a qualitative literature study method, by examining certain concepts, thoughts, experiences, or life events based on written information taken from reference books, proceedings, research reports, magazines, newspapers, journals, and other sources relevant to the research theme. The results of the study indicate that the concept of Saint Vincent's mortification is very relevant in the context of education and character formation. This concept emphasizes the importance of self-denial as the first step to building love for God and others. Moreover, mortification also helps individuals to train themselves in controlling egoism and directing attention to the needs of others. This concept can be a strong foundation for prospective catechists and religious teachers to live a life of faith, love, and commitment in service. This research is expected to be a reference for educators and coaches in designing character building programs based on deep spiritual values.